Analisa Pengaruh Preheating dan Post Weld Quench terhadap Kekuatan dan Struktur Mikro Baja S45C dengan Pengelasan Shielded Metal Arc Welding - Rachman, Arif; Dirja, Iman; Setiawan, Reza (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
In many industrial contexts, steel is an everyday material. The technique of attaching metal parts using heat energy, known as welding, is something we encounter often; S45C is one of several steels that are used in machine construction. Protected metal arc welding is one type of welding that we come across frequently. Unwanted metallurgical changes, deformation, or residual stress in the base metal might occur as a consequence of uneven or excessive heating. A better method is to heat it up beforehand, often known as preheating, before welding. Determining the effect of preheating on the hardness of S45C steel during welding is one of the primary aims of this study. (2) to understand how changes in temperature and time affect the microstructure of S45C steel during welding and how it affects the final product. (3) ascertain the effect of temperature and duration on the resulting hardness of S45C steel welding. During the preheating procedure, the temperature is varied between 160 and 260 degrees Celsius, and the waiting periods are 7, 15, and 20 minutes, respectively. Hardness and microstructure testing, also known as metalografy, is performed on S45C steel after shielded metal arc welding (SMAW) to ascertain the degree of hardness and microstructure of the steel.